2019
DOI: 10.1364/josab.37.000133
|View full text |Cite
|
Sign up to set email alerts
|

Propagation characteristics of vortex beams in anisotropic atmospheric turbulence

Abstract: The phase distortion of vortex beams caused by atmospheric turbulence is calculated by the power spectral inversion method. An analytical expression of the fundamental mode Gaussian vortex beam that propagates through anisotropic atmospheric turbulence has been deduced. The influences of altitude, anisotropic factor, and topological charge (TC) on the propagation characteristics of vortex beams are discussed in detail. The results show that when the altitude is in the region of 3–6 km, the change of altitude h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Fluctuation of electric field between two or more points can be considered as coherence of the light beams. The effect of coherence parameters is analyzed by different research groups [37,38]. The term of coherent vortex beam firstly was revealed by Coullet in 1989, then Allen found that vortex beams can carry OAM [39,40].…”
Section: Coherent Vortex Beams In Turbulent Mediamentioning
confidence: 99%
“…Fluctuation of electric field between two or more points can be considered as coherence of the light beams. The effect of coherence parameters is analyzed by different research groups [37,38]. The term of coherent vortex beam firstly was revealed by Coullet in 1989, then Allen found that vortex beams can carry OAM [39,40].…”
Section: Coherent Vortex Beams In Turbulent Mediamentioning
confidence: 99%